Evidence of Psychological Manipulation in the Process of Violent Radicalization: An Investigation of the 17-A Cell - González, Irene; Moyano, Manuel; Lobato, Roberto M.; Trujillo, Humberto M. (Frontiers in Psychiatry, 2022)
Introduction Radicalization leading to violence is a complex social process that frequently targets young people. In this study, we examine the 17-A cell, which carried out terrorist attacks in the Spanish cities of Barcelona and Cambrils on August 17, 2017. We focus on the psychological manipulation techniques used to radicalized members of the cell. Methods Using deductive content analysis, we examined the judicial order of the National High Court related to “Operation Ramblas” and the police proceedings of Cuerpo de Mossos d'Esquadra (CME) associated with the Barcelona and Cambrils attacks. Our goal was to determine whether psychological manipulation was used on the cell members and, if so, how frequently. Results Our results suggest that different psychological manipulation techniques were used on the 17-A cell members to facilitate their use of ideological violence. The most frequent strategies were cognitive control (control of attention, group identification, and denigration of critical thinking), environmental control (control of information), and emotional control (authoritarian leadership). Conclusions This study provides evidence that psychological manipulation techniques were used in the radicalization of 17-A cell members. The results are discussed in the context of previous research on the psychology of violent extremism and terrorism. We highlight the need for prevention and psychosocial interventions to steer young people away from violent extremism.